Long-Term Differential and Averaged Deformation of Box-Type Pre-stressed Concrete Exposed to Natural Environment - Hayasaka, Shuntaro; Maekawa, Koichi; Chijiwa, Nobuhiro (Journal of Advanced Concrete Technology, 2018)
Middle-scale box-sectional hollow PC ducts, which consist of heterogeneous concrete with different mix proportions, were exposed to natural environments for about three years, and the long-term curvature and axial mean deformation, which have much to do with deflection of long span bridge viaducts, was gaged for verification of coupled ther-mo-hygral and multi-scale models. The associated internal moisture and the local climate inside micro-pores were measured and the effect of precipitation was quantified over yearly four seasons. The moisture migration linked with concrete multi-scale mechanics was analyzed and the simulation results are compared with the field exposure tests. The reliability of the thermo-hygral analysis, which has been used for estimating the long-term serviceability of bridges, was made firmer.